Safety assessment of the biotechnologically produced human-identical milk oligosaccharide 3-Fucosyllactose (3-FL). (December 2019) - Pitt, J.; Chan, M.; Gibson, C.; Hasselwander, O.; Lim, A.; Mukerji, P.; Mukherjea, R.; Myhre, A.; Sarela, P.; Tenning, P.; Himmelstein, M.W.; Roper, J.M.
Abstract: 3-Fucosyllactose (3-FL), a highly abundant complex carbohydrate in human breast milk, functions as a prebiotic promoting early microbial colonization of the gut, increasing pathogen resistance and modulating immune responses. To investigate potential health benefits, 3-FL was produced by fermentation using a genetically modified E. coli K12 strain. The safety assessment of 3-FL included acute oral toxicity, in vitro and in vivo assessment of genetic toxicity, and a subchronic rodent feeding study. 3-FL was not acutely toxic at 5000 mg/kg bw, and there was no evidence of genetic toxicity in the bacterial reverse mutation test and chromosomal aberration assay. There was a repeatable statistically-significant trend in the 4-h S9-activated test conditions in the in vitro micronucleus assay; the confirmatory in vivo mouse micronucleus study was negative at all doses. Dietary subchronic exposure of rats to 3-FL (5% and 10%) did not produce any statistical or biologically-relevant differences in growth, food intake or efficiency, clinical observations, or clinical or anatomic pathology changes at average daily intakes of 5.98 and 7.27 g/kg bw/day for males and females, respectively. The weight of evidence from these studies support the safe use of 3-FL produced using biotechnology as a nutritional ingredient in foods. Highlights: 3-Fucosyllactose was assessed for genetic, acute and subchronic toxicity. No effects were observed in the AMES and chromosomal aberration assays. A positive trend observed in the in vitro micronucleus assay was not confirmed in the in vivo assay. The subchronic NOELs are 5.98 g/kg body weight/day (M) and 7.27 g/kg body weight/day (F).